The manuscript of Cassiodorus' Expositio Psalmorum preserved in Montpellier (Manuscrits Medievaux, ms. 5) (Edad Media. Revista de Historia, 2025)
The study of the manuscript containing the Expositio Psalmorum of Cassiodorus of Narbonese origin has revealed a series of paleographic and codicological characteristics that are of special interest for the understanding of early medieval Hispanic codices. The use of Visigothic and Carolingian scripts made simultaneously by the same copyist (a case of digraphism), together with the disorder found in the preservation of its quires, possibly due to a later binding, is noteworthy. These characteristics render it a particularly interesting case for the examination of various graphic issues, asit is a well-known codex that had not undergone a comprehensive analysis.
Keywords: Visigothic manuscript; Carolingian script; digraphy; Septimania; Cassiodorus